2014
DOI: 10.1002/pi.4669
|View full text |Cite
|
Sign up to set email alerts
|

Block architecture influence on the structure and mechanical performance of drawn polyurethane elastomers

Abstract: Some natural biopolymers such as spider silk exhibit superb mechanical properties, characterised by their great toughness. Synthetic polyurethane (PU) copolymers also endow great toughness but lack silk's stiffness and strength. The aim of this work was to elucidate the role of segment block architectural features that influence PU stiffness and strength after cold drawing. For this purpose PUs with varied soft segment character, crystalline versus rubbery, as well as with different hard segment chemistries, 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 39 publications
0
16
0
3
Order By: Relevance
“…Crystalline HDI–BD blocks are more hydrophobic and strongly trend to interassociate through hydrogen bonding . The elastic modulus of the materials resulted highly dependent on copolymer composition, increasing almost linearly with the content of HDI–BD crystalline segments.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…Crystalline HDI–BD blocks are more hydrophobic and strongly trend to interassociate through hydrogen bonding . The elastic modulus of the materials resulted highly dependent on copolymer composition, increasing almost linearly with the content of HDI–BD crystalline segments.…”
Section: Resultsmentioning
confidence: 89%
“…Other relevant physical properties are gathered in Table . It is observed that the molecular weights of the synthesized materials are typical of the two‐shoot synthesized segmented PU . The increase in stiffness of solid PU films increased notably with the increase of HDI–BD block content due to the increase in the hydrogen bonding between crystalline HDI–BD segments…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5b) donde el PU glicol mantiene valores de tensión superior durante la relajación de muestras deformadas hasta 200%, durante un periodo de al menos diez minutos. Los perfiles de Tensión vs. t en los que la tensión se mantienen elevada durante un largo periodo de tiempo sugiere que, en comparación con otros materiales en los que no se mantiene, la estructura está más cohesionada, bien mediante fases cristalinas o fuertes enlaces intermoleculares tales como puentes de hidrógeno [12]. El perfil de relajación del PU glicol nos indica nuevamente su estructura altamente enlazada por puentes de hidrógeno, en comparación con el PU macrodiol .…”
Section: Propiedades Mecánicasunclassified
“…La comprensión de la influencia de la naturaleza y de la arquitectura de los segmentos en la morfología y propiedades de los especímenes orientados es importante para entender su papel en las propiedades mecánicas resultantes [7]. Así por ejemplo mientras los PU formados por diisocianatos voluminosos como el 4,4´-difenil metano diisocianato (MDI) o por el isoforon diisocianato (IPDI) proporcionan baja cristalinidad en las unidades asociables por puentes de hidrógeno, segmentos formados por 1,6-hexametilen diisocianato (HDI) forman políme-ros con unidades cristalinas altamente asociadas por puentes de hidrógeno, que evolucionan en materiales más rígidos y resistentes tras su orientación macromolecular [12]. Estos resultados ponen de manifiesto la importancia de los puentes de hidrógeno en las propiedades mecánicas finales por lo que en el objetivo de biomimetizar la tenacidad de la seda de araña (150-300 MJ•m -3 ) [13] se debería desarrollar materiales con una alta densidad de puentes de hidrógeno pero que a su vez posean cierta elasticidad que proporcione tenacidad al material final, en contraposición a materiales como el Kevlar (50 MJ•m -3 ) o el Nailon (80 MJ•m -3 ) [14].…”
unclassified